Effects of temperature and storage duration on quality of an insect artificial diet - Ho, Khanh-Van; Hibbard, Bruce E.; Vella, Michael G.; Shelby, Kent S.; Huynh, Man P. (Frontiers in Insect Science, 2024)
Artificial diets are widely used to produce insects for research and education programs. Completed diets, in which the diets are fully made from individual ingredients and ready to use, often have high water activity, making them vulnerable to degradation. Proper storage is critical to maintaining diet quality, yet the storage conditions are not well investigated. In this study, we characterized the effects of storage conditions (temperatures and storage duration) on the quality of a diet capable of rearing both specialist and generalist insect species. The completed diet, produced by both private industry and a USDA-Agricultural Research Service laboratory, was exposed to varying temperatures during a 24-hour transit over 1600 km. After transit, it was stored at 4 °C for a total storage period of 28 days. In a separate experiment, the completed diet was stored immediately after diet production at five fixed temperatures (-20, 4, 22, 25, and 33 °C) for up to 28 days. For both experiments, at 5 intervals after storage (1, 7, 14, 21, and 28 days), diet quality was accessed by life history parameters (survival, molting, and weight) of western corn rootworm (Diabrotica virgifera virgifera LeConte) larvae, the most serious maize pest in the United States. Our results showed that exposure to varying temperatures between -2 °C and 27 °C for 24 hours had no significant impact on diet quality. However, extended storage (beyond 24 hours) at any of the fixed temperatures negatively affected diet quality. Insects reared on diets stored for over 24 hours at fixed temperatures ranging from -20 °C to 33 °C had significant declines in performance. Among the tested temperatures, -20 °C and 4 °C were found to be the most effective for preserving diet quality. At these low temperatures, there were no significant changes in insect weight and survival for diets stored within 21 and 28 days, respectively, though molting was significantly reduced within 7 days of storage. These findings provide the base of information on the storage conditions for completed diets, supporting the production of healthy insects.